Cinacalcet versus standard treatment for chronic kidney disease: a protocol for a systematic review and meta-analysis. Issue 1 (December 2016) - Sekercioglu, Nigar; Busse, Jason; Mustafa, Reem; Guyatt, Gordon; Thabane, Lehana
Abstract Background Chronic kidney disease-mineral and bone disorders (CKD-MBD) have been associated with poor health outcomes, including diminished quality and length of life. Standard management for CKD-MBD includes phosphate-restricted diet, active vitamin D, vitamin D analogs, and phosphate binders. Persistently elevated parathyroid hormone (PTH) levels may require the addition of Cinacalcet hydrochloride (cinacalcet) which sensitizes calcium receptors on the parathyroid glands. The objective of this systematic review is to compare the effect of cinacalcet versus standard treatment in patients with CKD-MBD. Methods/design Data sources will include MEDLINE, EMBASE, the Cochrane Register of Controlled Trials, and Web of Science from 1996 to June 2015. Teams of two reviewers will, independently and in duplicate, screen titles and abstracts and potentially eligible full text reports to determine eligibility, and subsequently abstract data and assess risk of bias in eligible trials. We will calculate the effect estimates (risk ratios or mean differences) and 95 % confidence intervals, as well as statistical measures of variability in results across studies using random effect models for patient-important and intermediate outcomes. We will use the GRADE (Grading of Recommendations, Assessment, Development and Evaluation) approach to rate the quality of evidence about estimates of effect on an outcome-by-outcome basis. We will present our results with a GRADE summary table. Discussion Our review will explore the effect of cinacalcet versus standard treatment in patients with CKD-MBD. The results of this systematic review will help guide management of this patient population, and identify targets for future research. Systematic review registration PROSPERO CRD42015020318http://www.crd.york.ac.uk/PROSPERO/display_record.asp?ID=CRD42015020318.